THE INTEGRITY OF THE ICE RECORD OF GREENHOUSE GASES WITH A SPECIAL FOCUS ON ATMOSPHERIC CO2 - Dominique Raynaud (Лëд и снег, 2015)
Over the last 25 years, the ice core record has provided a unique and precious archive of past changes in three important greenhouse gases: carbon dioxide CO2, methane CH4 and nitrous oxide N2O. Recovering the Vostok ice core has played a major role, being the first ice record showing the variations of CO2 and CH4 during a full glacial-interglacial cycle, and a few years later being extended to three more cycles. This information, by revealing the tight coupling between climate and carbon cycle during the last glacial-interglacial cycles, has become a benchmark against which climate and carbon cycle models can be tested. The purpose of the present work is to discuss the degree of integrity of the ice core record of greenhouse gases and to assess to which degree it provides an accurate reconstruction of the past atmospheric changes. The various processes potentially affecting the integrity of the record are discussed. They include the interactions of trace gases with precipitation or firn grains, the effect of summer-melting at the surface of the ice sheet, the diffusion and the gravitational setting of gases in the open spaces of the firn, the physical, chemical and biological interactions between the air trapped and the ice matrix, the role of the transformation of air bubbles into air hydrates with depth in the ice column. Providing to select an appropriate sampling site, to take specific precautions during storage and transportation of the ice cores, and to select ice of good quality, the ice core record of initial atmospheric gases is hardly affected by the processes listed above. Such conclusion is strongly supported by the remarkable agreement of global signals like CO2 or CH4 measured in different cores taken at different locations. Finally, I bring back here the history of how the ice core record of atmospheric CO2 has been obtained, from the pioneering times to today, and summarize the main conclusions reached in terms of climate – carbon cycle interactions.